In vivo absorptomics: Identification of bovine milk-derived peptides in human plasma after milk intake. (15th August 2022) - Caira, Simonetta; Pinto, Gabriella; Picariello, Gianluca; Vitaglione, Paola; De Pascale, Sabrina; Scaloni, Andrea; Addeo, Francesco
Highlights: Blood was sampled from N = 3 human volunteers following the intake of pasteurized milk. A clean-up strategy was developed to detect milk-derived peptides circulating in blood. Hundreds of milk-derived peptides circulating in plasma identified by MS ("absorptomics"). Many circulating milk-derived peptides can be involved in a range of biological activities. BCM-7 and BCM-5 were not detected in the plasma, differently from many BCM precursors. Abstract: A dedicated two-step purification procedure prior to nanoliquid chromatography-electrospray-tandem mass spectrometry analysis enabled the identification of bovine milk-derived peptides absorbed and circulating in the plasma of three healthy volunteers who received 250 mL of pasteurized milk after a 10-days washout. The appearance and clearance of milk peptides in plasma were monitored at various time points. Overall, 758, 273 and 212 unique peptides derived from 15, 15 and 18 bovine milk proteins, respectively, were identified in the plasma of these volunteers, evidencing a substantial inter-individual variability. Peptides encrypting possible bioactive and/or immunogenic molecules originating from caseins, β-lactoglobulin and minor milk proteins were detected. Peptide representation data revealed the combined action of endoproteases involved in primary hydrolysis during gastroduodenal digestion and exopeptidases that hydrolyse peptides in the small intestine. It remains to be established whether the half-life and concentration ranges of circulating milk-derived peptides may have any impacts on human health.